THE COMPOSITION GOMBANG IN THE AFTERNOON AND NIGHT IN VILLAGE BANTAR SUB DISTRICT, WEST RANSANG, RIAU PROVINCE - Efry Juliansyah; Bustar Bustar; Pareng Rengi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRAC The research was conducted in August 2017 in Bantar Village, West Rangsang Subdistrict, Meranti Island, Riau Province. This study aims to determine the types of composition of the catch of waves operated day and night in Bantar Village, Ransang District, western District of Kepulauan Meranti, Riau Province. The method used in this research is survey and research conducted during 6 days of capture. The catch during the study was 141.34 kg (15541). Result of research of composition of catch Gombang during the day is 51.49 kg (7656 head), while at night 89.85 kg (7950 head). The catch consists of fifteen species. Night catches are bigger than daytime catches. Their catches are lomek fish (Horpodon neherus), prawn thorn (Alphases sp), fish kitang (Scatophagus argus), fish senutang (Lutjanidae campechanus), red shrimp (Paneus monodon), White shrimp (Penaus merguininsis), lobster (Nephropidae) , fish mackerel (Cybium commersoni), sea fish (Steppina breniceps), fish selangat (Chirocentrus dorab), layur fish (Thirchius savala), crabs (Portunidae), octopus (loligo sp), fish thorn (Arius caelatus), white pomfret (Pampus argentus). Keywords: Gombang, Composition Catch Fish, Afternoon and Night Period, village Bantar